Adipose-Derived Stem Cells From Patients With Ulcerative Colitis Exhibit Impaired Immunosuppressive Function - Wu, Xiaoyun; Mu, Yongxu; Yao, Jingyi; Lin, Fuhong; Wu, Daocheng; Ma, Zhijie (Frontiers in Cell and Developmental Biology, 2022)
Adipose-derived stem cells (ADSCs) are able to modulate the immune response and are used for treating ulcerative colitis (UC). However, it is possible that ADSCs from patients with inflammatory or autoimmune disorders may show defective immunosuppression. We investigated the use of ADSCs from UC patients for autologous cell treatment, specifically, ADSCs from healthy donors (H-ADSCs) and UC patients (P-ADSCs) in terms of various functions, including differentiation, proliferation, secretion, and immunosuppression. The efficacy of P-ADSCs for treating UC was examined in mouse models of acute or chronic colitis. Both H-ADSCs and P-ADSCs were similar in cell morphology, size, adipogenic differentiation capabilities, and cell surface markers. We found that P-ADSCs had lower proliferative capacity, cloning ability, and osteogenic and chondrogenic differentiation potential than H-ADSCs. P-ADSCs exhibited a diminished capacity to inhibit peripheral blood mononuclear cell proliferation, suppress CD25 and CD69 marker expression, decrease the production of inflammation-associated cytokines interferon-γ and tumor necrosis factor-α, and reduce their cytotoxic effect on A549 cells. When primed with inflammatory cytokines, P-ADSCs secreted lower levels of prostaglandin E2, indoleamine 2, 3-dioxygenase, and tumor necrosis factor-α–induced protein 6, which mediated their reduced immunopotency. Moreover, P-ADSCs exhibited weaker therapeutic effects than H-ADSCs, determined by disease activity, histology, myeloperoxidase activity, and body weight. These findings indicate that the immunosuppressive properties of ASCs are affected by donor metabolic characteristics. This study shows, for the first time, the presence of defective ADSC immunosuppression in UC, indicating that autologous transplantation of ADSCs may be inappropriate for patients with UC.